Comparative morphometry of cerebral microvessels in atherosclerotic and diabetic encephalopathies. - Shavrin, V. A.; Avramenko, Yu. N. (Морфологія / Morphologia / Morfologìâ, 2017)
Background. Identification of features in the morphology and morphogenesis of various discirculatory encephalopathies is one of the actual problems of scientific and practical neuromorphology. Objective. The work is devoted to a comparative analysis of the morphometric parameters of the vessels of the arteriolar segment of the microcirculatory bed of the cerebral cortex in atherosclerotic and diabetic encephalopathies. Methods. Morphometric examination of microvessels was performed in 30 sectional cases with atherosclerotic and diabetic encephalopathy and group of conditional control without cerebral vascular pathology. Transverse profiles of arterioles of 3-5 layers of the cerebral cortex of the right parietal lobe were measured. The results of morphometry were subjected to statistical treatment. Results. In diabetic and atherosclerotic encephalopathies the thickness of the microvessel walls increases, the outer wall increases and the inner diameters decrease, the indices of the internal and external Form Factors decrease, Vogenvort index and Kernogan index significantly increase in comparison with the control observations. The thickening of microvessel walls compared with the norm is much more pronounced in diabetic encephalopathy than in atherosclerotic (by 110.2% and by 67.8%, respectively), the difference is 42.4%. The thickening of the vascular walls is accompanied by a decrease in the diameter of the lumen of the microvessels - by 10% for diabetic and 10.5% for atherosclerotic encephalopathy compared with the norm (the difference between encephalopathies is statistically unreliable). Reduction of the indices of the external and internal Form Factor of the vascular walls compared with the norm is insignificant and its degree does not depend on the nature of encephalopathy. The increase in Vogenvort and Kernohan indices compared with the norm is typical for both encephalopathies, but more sharply expressed in diabetic patients, which indicates a more severe disturbance of microcirculation. Conclusion. The presented data indicate that a number of changes appear in the arteriolar segment of the microcirculatory bed of the deep layers of the cerebral cortex that characterize a significant decrease in the cortical microcirculation in atherosclerotic and diabetic encephalopathies.